Unintentional injuries at home and in the preschool setting: Greek ECEC professionals’ and preschoolers’ parents’ knowledge and attitudes towards first aid - Konstantina Rentzou; George Daglas (Journal of Childhood, Education & Society)
Although safety of home and preschool setting is a key quality indicator of the two main environments in which preschoolers spend most of their day, most unintentional injuries during early childhood take place in these two settings. Thus, despite the frequency of accidents during early childhood, scarce research has explored both the epidemiology of childhood injuries and the knowledge and attitudes of ECEC professionals’ and preschoolers’ parents towards first aid. Acknowledging this gap in literature, the present study aimed at exploring 74 Greek ECEC professionals’ and 213 preschoolers’ parents’ knowledge and attitudes towards first aid. In addition, the study aimed at mapping the most frequently occurring accidents both at home and at preschool, as well as the places withing these two settings where most of the accidents happen. Results of the present study indicate that although participants have positive attitudes towards first aid, and most of them have been trained in first aid, their knowledge of handling accidents and other health related issues is limited. In addition, the results showed accidents rarely happen at home and at preschool. The accidents that have been reported to occur take place during children’s free play. The most common places where accidents occur are in the living room and the kitchen. The results highlight the need for frequent training both for parents and ECEC professionals, for intersectoral collaboration between health and education organizations to design interventions and for awareness raising campaigns.